Patient factors associated with weight gain and weight loss after knee or hip arthroplasty. Issue 4 (July 2019) - Naylor, Justine M.; Mills, Kathryn; Pocovi, Natasha; Dennis, Sarah; Hackett, Danella; Hassett, Leanne; Brady, Bernadette; Lewin, Adriane M.; Adie, Sam; Xuan, Wei
Highlights: Most TKA and THA patients are overweight or obese prior to surgery yet few experience meaningful weight loss long-term. Factors associated with significant weight gain are different to those for weight loss, thus weight management is complex. Of the new factors examined, only the absence of ongoing index joint issues was associated with weight loss. Abstract: Objectives: Following total knee or total hip arthroplasty (TKA, THA), up to 31% of recipients experience significant weight gain while up to 14% experience significant weight loss. Factors associated with significant weight change (≥5% of baseline weight) have not been comprehensively explored. This study aimed to identify pre- and post-surgical (including current) patient factors associated with significant weight change three years after surgery. Methods: A pre-existing nationally-acquired cohort who underwent TKA or THA for osteoarthritis participated in 3-year telephone follow-up. Updated weight, comorbidity, and complication data were collected along with ongoing index joint problems and other patient-reported outcomes including global improvement. These data, along with body mass index (BMI) pre-surgery and post-surgery rehabilitation received, were incorporated into two multivariable logistic regression models to determine separately the factors associated with ≥5% weight gain and ≥5% loss at 3-years post-surgery. Results: 73.4% (1289/1757) participated in the follow-up; 1191 (n = 663 TKA) provided updated weight data. Patterns of weight change were similar for both surgeries (TKA: 16.1% gained ≥5%, 19.6% lost ≥5%; THA: 15.8% gained ≥5%, 17.8% lost ≥5%). In multivariable modelling, younger age and lower pre-surgery BMI were significantly associated with weight gain; female gender and an absence of ongoing index joint issues were associated with weight loss. Conclusion: Different mechanisms are likely associated with significant weight gain or loss at 3-years post-surgery. Cogent weight management entails consideration of both outcomes. Many post-surgical factors appear not to be importantly associated with weight change.